MATHEMATICAL MODELING OF ECCENTRICALLY LOADED GROUNDS ON LAYERED FOUNDATIONS BY FINITE ELEMENT METHOD - Andrieiev, V. S.; Tiutkin, O. L.; Selikhova, T. O. (Science and Transport Progress, 2004)
The article considers the issues of mathematical modelling of behaviour the outside-of-the-centre loaded basements, resting on multi-layer beds. It has been shown that application of the finite elements method forcalculation of such basements allows to get the results, most adequate to real conditions.